2014
DOI: 10.1111/jgs.12767
|View full text |Cite
|
Sign up to set email alerts
|

Pantoprazole Sodium–Induced Hyponatremia in a Frail Elderly Adult

Abstract: Crusted scabies is another important differential in any elderly adult with an itchy, psoriasiform scalp eruption. Individuals at higher risks include those who are bedbound with multiple medical comorbidities and poor mobility.The prognosis in MF is worse in men, older adults, at a higher stage of disease, and with the folliculotropic variant of MF. 2 This woman had at least T3N1M0B0 disease, compatible with Stage IIB, which is advanced. 4 Overall survival at this stage is 37.8% to 63.2% at 5 years after dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…More recently, there were also reports of hyponatremia related to esomeprazole and pantoprazole4,5. In the case of the latter, a frail elderly adult achieved normal serum sodium levels three months after stopping treatment with pantoprazole5. In our case, serum sodium levels reached normal values two months after the suspension of pantoprazole.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…More recently, there were also reports of hyponatremia related to esomeprazole and pantoprazole4,5. In the case of the latter, a frail elderly adult achieved normal serum sodium levels three months after stopping treatment with pantoprazole5. In our case, serum sodium levels reached normal values two months after the suspension of pantoprazole.…”
Section: Discussionsupporting
confidence: 62%
“…According to Naranjo Criteria5, there is a possible relation between hyponatremia and pantoprazole in this case report.…”
Section: Case Reportmentioning
confidence: 57%
See 2 more Smart Citations
“…However, with long-term use several adverse effects are reported, such as a changed gut microbiome, fundic mucosal hypertrophy, Clostridium difficile infection, vitamin B12 deficiency, hypomagnesemia, and acute interstitial nephritis [11]. There are only a few reports on PPI-induced hyponatremia with either omeprazole or pantoprazole [12][13][14][15]. Durst et al reported the reoccurrence of hyponatremia after reintroducing omeprazole [12].…”
Section: Discussionmentioning
confidence: 99%